Organization theory and design - Daft, Richard L. (Cincinnati, Ohio : South-Western College, 2001)
Introduction and organization theory. Organizational purpose and structural design. Open system design elements. Internal design elements. Managing dynamic processes.
Keywords: Organization; Sociology; Organization; Organizational sociology -- Case studies